Bond Strength between CAD/CAM PMMA Denture Base Resins and Characterisation Composites - Mei Ting Pong; Anastasiia Grymak; John Neil Waddell; Joanne Jung Eun Choi (MDPI AG, 2022)
Aim: To measure the bond strength between two different CAD/CAM PMMA denture base resins and three different types of gum characterisation composites. Materials and Methods: CAD/CAM single cross-linked (Telio CAD) and double cross-linked (Vivodent CAD) resins were prepared, obtaining a total of 180 bar specimens. Each specimen was prepared according to the manufacturer's instructions. The specimens were bonded to three different characterisation composites with varying viscosities; Kulzer Pala-creactive (P), Ivoclar SR Nexco (S), Shofu Ceramage (F). All the specimens were then tested using a chevron-notched three-point bond strength test in a universal testing machine to obtain fracture energy release toughness (MPa√m) and bond strength (MPa). The specimens were thermocycled to simulate 6 and 12 months of ageing in vivo. The results were statistically analysed (SPSS). The fractured surfaces of the tested specimens were examined with a scanning electron microscope (SEM) to evaluate the failure modes. Results: Pala-creactive characterisation composites showed the highest overall bond strength (3.49 ± 0.86 MPa) and fracture toughness (1.59 ± 0.34 MPa√m) when bonded to both CAD PMMA denture resins, which were statistically higher than the values obtained when they were bonded to Telio (p < 0.001). The Ceramage composite showed the lowest bond strength (1.05 ± 0.59 MPa) and fracture toughness (0.47 ± 0.4 MPa√m). The dominant mode of failure for all groups was mixed. Conclusion: Single cross-linked PMMA (Telio) showed a higher overall bond strength compared to double cross-linked PMMA when bonded to three different characterisation composites. Telio CAD showed a clear bond strength decrease after 6 and 12 months of artificial ageing, while Vivodent CAD showed a bond strength increase.